EXPLORING THE CONNECTION BETWEEN POSITIVE PSYCHOLOGY INTERVENTIONS AND WORKPLACE HAPPINESS - Nikhil Joshi; Meera Gupta; Haruto Takahashi (Yayasan Adra Karima Hubbi, 2026)
Workplace happiness is a critical factor that influences employee engagement, productivity, and overall organizational success. Positive psychology interventions (PPIs), which focus on enhancing well-being and personal strengths, have been shown to improve individual happiness. However, the specific connection between PPIs and workplace happiness remains underexplored. Understanding how these interventions impact happiness in the workplace is crucial for organizations seeking to improve employee satisfaction and organizational outcomes. This study aims to explore the connection between positive psychology interventions and workplace happiness. The research investigates whether the implementation of PPIs leads to improved emotional well-being, job satisfaction, and overall happiness among employees. A mixed-methods approach was employed, involving both quantitative surveys and qualitative interviews. Data were collected from 250 employees across various industries who participated in a 6-week PPI program. The findings revealed that employees who participated in the PPI program reported significant increases in workplace happiness, job satisfaction, and emotional well-being. The study concludes that positive psychology interventions are effective in enhancing workplace happiness and can be a valuable tool for organizations seeking to improve employee well-being and performance.